Case report: Thrombolysis in patients with acute ischemic stroke and cerebral cavernous malformation - Lin, Jie; Weng, Xiongpeng; Zheng, Jing; Wu, Saizhen; Bao, Qiongqiong; Peng, Feifei; Huang, Yanbin (Frontiers in Neurology, 2023)
Background Cerebral cavernous malformation (CCM) is a rare disease associated with a latent risk of intracranial hemorrhage. However, due to limited evidence, the safety of recommending intravenous tissue plasminogen activators for patients with acute stroke and CCM remains uncertain. Methods Our study identified five patients with acute stroke and CCM treated between 2017 and 2023 across two hospitals. A comprehensive literature review was conducted, incorporating three similar case reports and two retrospective studies. Results Among 30 patients reviewed, three exhibited symptomatic intracranial hemorrhage, two of whom were women. Additionally, three patients presented with calcification in their CCM, with two experiencing symptomatic intracranial hemorrhage. Conclusion The observed incidence of symptomatic intracranial hemorrhage following intravenous tissue plasminogen activator administration appears to be elevated in patients with CCM. Therefore, before thrombolysis, a thorough evaluation of personalized risk–benefit ratios is crucial. Furthermore, conducting further research involving multiple centers and larger sample sizes is imperative to advance our understanding in this area, especially in identifying hemorrhage risk factors.